Influence of enamel/dentin thickness on the toxic and esthetic effects of experimental in-office bleaching protocols - de Oliveira Duque, C. C. [UNESP]; Soares, D. G. [UNESP]; Basso, F. G. [UNESP]; Hebling, J. [UNESP]; de Souza Costa, C. A. [UNESP] (Springer Nature, 2017)
Objectives: This paper aims to assess the whitening effectiveness and toxicity of tooth-bleaching protocols applied to enamel/dentin disks simulating mandibular incisors (ICs) and premolars (PMs). Materials and methods: A 10% hydrogen peroxide (H2O2) gel was applied for 3 × 15, 1 × 15, or 1 × 5 min to enamel/dentin disks simulating mandibular ICs and PMs, and the trans-enamel and trans-dentinal diffusion products were applied to human dental pulp cells (1 h). Professional therapy (35% H2O2—3 × 15 min) was used as positive control, and non-bleached samples were used as negative control. Cell viability and morphology, oxidative stress generation, and odontoblastic marker expression were assessed. The H2O2 diffusion and enamel color change (ΔE) were also analyzed. Results: The 10% H2O2 gel induced significant cell viability reduction only when applied 3 × 15 min, with the intensity of oxidative stress and down-regulation of odontoblastic markers being higher in the IC group. The other experimental bleaching protocols caused slight alterations regarding the cell parameters evaluated, with intensity being related to enamel/dentin thickness. These effects were also correlated with higher H2O2 diffusion in the IC group. ΔE values similar as positive control were found for the 10% 3 × 15 and 1 × 15 protocols on IC group, after 4 and 6 sessions. Conclusion: Application of a 10% H2O2 bleaching gel for 15 or 45 min to thin dental substrate significantly minimizes cell toxicity in comparison with highly concentrated gels associated with similar esthetic outcomes by increasing the number of bleaching sessions. Clinical relevance: Bleaching gels with 10% H2O2 applied in small teeth for short periods may be an interesting alternative to obtain whitening effectiveness without causing toxicity to pulp cells, which may be able to reduce the tooth hypersensitivity claimed by patients.
Keywords: Cell differentiation; Cytotoxicity; Dental pulp; Tooth bleaching